1956
DOI: 10.1017/s000748530003710x
|View full text |Cite
|
Sign up to set email alerts
|

The Persistence and Fate of DDT on Foliage. II.—Comparative Rates of Loss of DDT Deposits from Glass Plates and Growing Leaves

Abstract: A method is described of applying even deposits of insecticide to leaves without detaching the leaves from the plants. The insecticide is sprayed by hand from an air-operated paint-spray gun under controlled conditions. Using this method for applying the insecticide, the persistence of DDT on living leaves and on glass plates was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1962
1962
1975
1975

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A small proportion of the leaves that had been very close to the spraying lance had received applications so excessive that the insecticide had run off the leaves; such leaves were discarded as they were very much in the minority. No attention was paid to which plants were sampled as it has been shown that differences in toxicity between various leaf surfaces can be very small provided the deposits are of the same concentration and without oil carriers (Ward & Burt, 1955).…”
mentioning
confidence: 99%
“…A small proportion of the leaves that had been very close to the spraying lance had received applications so excessive that the insecticide had run off the leaves; such leaves were discarded as they were very much in the minority. No attention was paid to which plants were sampled as it has been shown that differences in toxicity between various leaf surfaces can be very small provided the deposits are of the same concentration and without oil carriers (Ward & Burt, 1955).…”
mentioning
confidence: 99%
“…Where the ovicidal effect of a material was to be tested, shoots bearing eggs were selected, or female mites were placed on the shoots and left there until sufficient eggs had been laid. The spray was applied as a fine mist to the entire upper surface of the single leaf by the method of Burt & Ward (1956) for depositing an even film on attached leaves. An ' Air-brush ' equipment delivered 2 ml.…”
Section: Experimental Methodsmentioning
confidence: 99%